The Effect of Processing Additives on Energetic Disorder in Highly Efficient Organic Photovoltaics: A Case Study on PBDTTT‐C‐T:PC71BM. (27th May 2015) - Gao, Feng; Himmelberger, Scott; Andersson, Mattias; Hanifi, David; Xia, Yuxin; Zhang, Shaoqing; Wang, Jianpu; Hou, Jianhui; Salleo, Alberto; Inganäs, Olle
<x xml:space="preserve">Abstract</x> Energetic disorder, an important parameter affecting the performance of organic photovoltaics, is significantly decreased upon the addition of processing additives in a highly efficient benzodithiophene‐based copolymer blend (PBDTTT‐C‐T:PC71BM). Wide‐angle and small‐angle X‐ray scattering measurements suggest that the origin of this reduced energetic disorder is due to increased aggregation and a larger average fullerene domain size together with purer phases.